Investigations of TiO₂, Ti/TiO₂, and Ti/TiO₂/Ti/TiO₂ coatings produced by ALD and PVD methods on Mg-(Li)-Al-RE alloys substrates - Marcin Staszuk; Łukasz Reimann; Aleksandra Ściślak; Justyna Jaworska; Mirosława Pawlyta; Tomasz Mikuszewski; Dariusz Kuc; Tomasz Tański; Antonín Kříž (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
Magnesium alloys have recently become increasingly popular in many sectors of the industry due to their unique properties, such as low density, high specific strength, vibration damping ability along with their recyclability and excellent machinability. Nowadays, thin films have been attracting more attention in applications that improve mechanical and corrosion properties. The following alloys were used for the coated Mg-Al-RE and the ultra-light magnesium-lithium alloy of the Mg-Li-Al-RE type. A single layer of TiO2 was deposited using the atomic layer deposition ALD method. Multiple layers of the Ti/TiO₂ and Ti/TiO₂/Ti/TiO₂ type were obtained by the MS-PVD magnetron sputtering technique. Samples were investigated by scanning and a transmission electron microscope (SEM, TEM) and their morphology was studied by an atomic forces microscope (AFM). Further examinations, including electrochemical corrosion, roughness and tribology, were also carried out. As a result of the research, it was found that the best electrochemical properties are exhibited by single TiO2 layers obtained by the ALD method. Moreover, it was found that the Ti/TiO₂/Ti/TiO₂ double film has better properties than the Ti/TiO₂ film.